Developing English Material for Food and Beverage Service for XI Grade Students of SMK SMSR Ubud - Gusti Ayu Putu Ari Utami; Nyoman Adi Jaya Putra; Dewa Putu Ramendra (Indonesian Journal Of Educational Research and Review, 2020)
This study aimed at describing the English for Food and beverage service materials needed by students of SMK SMSR Ubud, describing how the materials were developed, and analysing the quality of the developed materials. This study used research and development model suggested by (Richey and Klein, 2007) comprising design, development and evaluation. The instruments used were questionnaires, interview guides, document analysis, and checklist. The findings of this study show that there were 7 topics needed to be developed included Preparing restaurant area, preparing and set up table, greet the guest, taking order, serving food, closing restaurant area, and non-alcoholic beverage. The materials were designed by following the English for Specific Purposes (ESP) material design suggested by Hutchinson and Waters (1987) involving input, content focus, language focus and task. Since English for food and beverage is part of ESP that is under English for Occupational Purposes, the effectiveness of the developed materials was evaluated using the criteria of good ESP materials suggested by Litz (2005), Hutchinson and Waters (2008), and Tomlinson (2009). After gaining the scores from the expert judges, the data then used the categorization of good teaching materials proposed by Nurkancana and Sunartana (2011). The quality of the developed materials was categorized as good material. Thus, it can be used as a main source for learning English Food and beverage service at SMK SMSR Ubud.